2014
DOI: 10.1021/es402809u
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Free, Conjugated, and Halogenated Estrogens in Secondary Treated Wastewater Effluent

Abstract: Steroidal estrogens are potent endocrine-disrupting chemicals that enter natural waters through the discharge of treated and raw sewage. Because estrogens are detrimental to aquatic organisms at sub-nanogram per liter concentrations, many studies have measured so-called "free" estrogen concentrations in wastewater effluents, rivers, and lakes. Other forms of estrogens are also of potential concern because conjugated estrogens can be easily converted to potent free estrogens by bacteria in wastewater treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…10,74 Due to the great difference between lipophilic free estrogens and hydrophilic estrogen conjugates, and highly broad range of polar and nonpolar property of them, reverse-phased absorbents were suitable for retaining targeted compounds due to the polymeric fillings. 71 An Oasis HLB, Strata-X, Supel™-Select HLB were selected and studied further by extracting 10 mL spiked Milli-Q water at concentration of 1 µg L −1 . The result (Table 3) showed that Oasis HLB achieved satisfactory recoveries (89.3%-102.8%) for chosen compounds reproducibility was with relative standard deviation (RSD) value less than 9.72%, having better performance than Stata-X (65.8%-110.3%) and Supel™-Select HLB cartridges (74.5%-103.3%).…”
Section: Optimisation Of Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,74 Due to the great difference between lipophilic free estrogens and hydrophilic estrogen conjugates, and highly broad range of polar and nonpolar property of them, reverse-phased absorbents were suitable for retaining targeted compounds due to the polymeric fillings. 71 An Oasis HLB, Strata-X, Supel™-Select HLB were selected and studied further by extracting 10 mL spiked Milli-Q water at concentration of 1 µg L −1 . The result (Table 3) showed that Oasis HLB achieved satisfactory recoveries (89.3%-102.8%) for chosen compounds reproducibility was with relative standard deviation (RSD) value less than 9.72%, having better performance than Stata-X (65.8%-110.3%) and Supel™-Select HLB cartridges (74.5%-103.3%).…”
Section: Optimisation Of Extraction Methodsmentioning
confidence: 99%
“…It was consistent with the chromatographic profiles reported in previous methods for measurement of both free and conjugated estrogens, wherein up to 45 min gradient was used for each injection. 28,63,65,[71][72][73] Though the C18 column did not allow complete baseline separation of the chosen compounds, especially for E2-DMIS and EE2-DMIS as well as E1-3S and E2-3S, they could be differentiated by mass spectrometric signal by the different m/z values of respective precursor ion and additionally by their specific fragmentation pathway upon MS 2 fragmentation of their precursor ions.…”
Section: Chromatographic Profiling Of Estrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard appears as a peak at 9.17 min in the intracellular extract ( Figure S6B), but in this case is entirely absent from the extracellular extract ( Figure S6D). Matrix effects are a potential concern when calibration solutions made in solvent are applied to the quantitation of analytes in a seawater or other complex matrix (Griffith et al, 2014). As noted above, we have investigated the significance of matrix effects in our targeted metabolomics method but full discussion of these results are beyond the scope of this paper (Johnson, Kido Soule, & Kujawinski, unpublished).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…SPE was most common sample preparation method for the determination of estrogens . Aminopropyl‐silica , C 18 ‐bonded silica , cross‐linked styrene and divinylbenzene were used as SPE adsorbents. Large amount of organic solvent was necessary for SPE.…”
Section: Introductionmentioning
confidence: 99%